The offering of incense make : Jewish mystical perspectives on disease and healing. Issue 2 (8th June 2022) - Ackermann, Domenik
Abstract: An examination of a passage from the Zohar on Exodus (2:218b‐219b) provides Jewish mystical perspectives on disease, which may help inform a Christian response of solace and healing to illness and suffering in general, and to the COVID‐19 pandemic in particular. The aforementioned passage in the Zohar describes the preparation of incense. The primary purpose of the portion maintains that incense has special healing powers that even relieve people from severe diseases. The relating Midrash Ha‐Ne'lam explains the passage further by referring to the 4th century Palestinian Rabbi Aha arriving at a town that struggles with an epidemic. It describes how R. Aha initiates a ritual containing a study of the Talmud on incense, after which the village is healed from the epidemic. The Jewish theological background and reception of the passage may shed new light on how ritual and sensory experience can alleviate the experience of disease and suffering.